Examining the Interaction Between Financial Literacy and Financial Risk Tolerance with Emphasis on the Moderating Effect of Financial Intelligence - Shahmohammadi, Moein; Torgheh, Soheila; Khatiri, Mohammad (Business, Marketing, and Finance Open, 2027)
This study aimed to examine the relationship between financial literacy and financial risk tolerance among employees of the Tehran Stock Exchange, with emphasis on the moderating effect of financial intelligence. This applied study used a descriptive-survey and causal-correlational design. The statistical population consisted of employees of the Tehran Stock Exchange, from whom 295 respondents participated in the final analysis. Data were collected using standardized questionnaires measuring financial literacy, financial risk tolerance, and financial intelligence. The validity of the instruments was assessed through expert review, convergent validity, and discriminant validity, while reliability was evaluated using Cronbach’s alpha and composite reliability. Data analysis was conducted using SPSS 22 and Visual PLS. Descriptive procedures were used for preliminary data screening, and partial least squares structural equation modeling was applied to test the measurement model, structural model, and moderating effect. The Kolmogorov–Smirnov test showed that the study variables did not follow a normal distribution, supporting the use of PLS-SEM. The structural model showed acceptable explanatory and predictive power, with financial risk tolerance having an R² value of 0.645 and a Q² value of 0.181. The overall goodness-of-fit index was 0.625, indicating strong model fit. Hypothesis testing showed that financial literacy had a positive and statistically significant relationship with financial risk tolerance (β = 0.527, t = 7.82, p = 0.000). However, the moderating effect of financial intelligence on the relationship between financial literacy and financial risk tolerance was not statistically significant (β = -0.053, t = 0.89, p = 0.370). The findings indicate that financial literacy is an important predictor of financial risk tolerance, but financial intelligence does not significantly change the strength or direction of this relationship. Therefore, improving financial literacy may be a direct and practical pathway for enhancing informed financial risk tolerance.